Elevated temperature characteristics of steel reinforcement incorporating threaded mechanical couplers - Bompa,DV; Elghazouli,AY (Fire Safety Journal, 2019)
This paper presents an experimental study into the influence of elevated temperatures on the mechanical properties of hot-rolled steel reinforcement which is spliced using two alternative types of threaded couplers. The investigation includes tests performed under steady-state and transient elevated temperature conditions for reinforcement bars of 16mm and 20mm diameter. For comparison purposes, tests carried out under ambient conditions and for non-spliced reinforcement bars are also included in the study. After describing the experimental arrangement and instrumentation, including purpose-adapted digital image correlation techniques, a detailed account of the test results is given. In addition to offering a direct evaluation of the temperature-dependent stiffness and strength properties, the test results provide an assessment of the complete stress-strain response. The strain hardening and ductility properties are also determined as a function of temperature for both spliced and non-spliced specimens. It is shown that the presence of couplers typically influences the ductility characteristics of threaded splices at elevated temperature as a function of the type and geometry of the couplers, whilst the stiffness and strength properties are largely similar to those of their non-spliced counterparts. The performance characteristics obtained from the detailed test measurements are used within the discussions to highlight issues relevant for application in practice.